Mutant KRAS Circulating Tumor DNA Is an Accurate Tool for Pancreatic Cancer Monitoring. (25th January 2018) - Perets, Ruth; Greenberg, Orli; Shentzer, Talia; Semenisty, Valeria; Epelbaum, Ron; Bick, Tova; Sarji, Shada; Ben‐Izhak, Ofer; Sabo, Edmond; Hershkovitz, Dov
Abstract : Background: Many new pancreatic cancer treatment combinations have been discovered in recent years, yet the prognosis of pancreatic ductal adenocarcinoma (PDAC) remains grim. The advent of new treatments highlights the need for better monitoring tools for treatment response, to allow a timely switch between different therapeutic regimens. Circulating tumor DNA (ctDNA) is a tool for cancer detection and characterization with growing clinical use. However, currently, ctDNA is not used for monitoring treatment response. The high prevalence of KRAS hotspot mutations in PDAC suggests that mutant KRAS can be an efficient ctDNA marker for PDAC monitoring. Subjects, Materials, and Methods : Seventeen metastatic PDAC patients were recruited and serial plasma samples were collected. CtDNA was extracted from the plasma, and KRAS mutation analysis was performed using next‐generation sequencing and correlated with serum CA19‐9 levels, imaging, and survival. Results : Plasma KRAS mutations were detected in 5/17 (29.4%) patients. KRAS ctDNA detection was associated with shorter survival (8 vs. 37.5 months). Our results show that, in ctDNA positive patients, ctDNA is at least comparable to CA19‐9 as a marker for monitoring treatment response. Furthermore, the rate of ctDNA change was inversely correlated with survival. Conclusion : Our results confirm that mutant KRAS ctDNA detection in metastatic PDAC patients is a poor prognostic marker. Additionally, we were able to show that mutant KRAS ctDNA analysis can be used to monitor treatment response in PDAC patients and that ctDNA dynamics is associated with survival. We suggest that ctDNA analysis in metastatic PDAC patients is a readily available tool for disease monitoring. Implications for Practice: Avoiding futile chemotherapy in metastatic pancreatic ductal adenocarcinoma (PDAC) patients by monitoring response to treatment is of utmost importance. A novel biomarker for monitoring treatment response in PDAC, using mutant KRAS circulating tumor DNA (ctDNA), is proposed. Results, although limited by small sample numbers, suggest that ctDNA can be an effective marker for disease monitoring and that ctDNA level over time is a better predictor of survival than the dynamics of the commonly used biomarker CA19‐9. Therefore, ctDNA analysis can be a useful tool for monitoring PDAC treatment response. These results should be further validated in larger sample numbers. Abstract : Circulating tumor DNA (ctDNA) is a tool for cancer detection and characterization with growing clinical use; however, ctDNA is not used for monitoring treatment response. This article reports serial monitoring of quantitative mutant KRAS ctDNA levels in patiets with metastatic pancreatic ductal adenocarcinoma and compares results to known markers such as CA19‐9.